PENYELESAIAN SENGKETA SYIQAQ ANTARA SUAMI ISTRI DALAM PERKAWINAN DITINJAU MENURUT HUKUM ISLAM (STUDI PADA DESA MEUNASAH PAPEUN KECAMATAN KRUENG BARONA JAYA KABUPATEN ACEH BESAR PROVINSI ACEH) - LENY NOVIANTI (PREMISE LAW JURNAL, 2017)
ABSTRACT Syiqaq or dispute between husband and wife in a marriage can be caused by nusyuz from the husband’s side or from the wife’s side. The result of the research shows that the incidence of syiqaq between husband and wife at Meunasah Papeun village is caused by nusyuz in the form of what has been said or infidelity. The position of the marriage during the syiqaq, according to the Islamic law, is still legitimate for the husband as long as he complies with the requirements for a marriage, while for the wife,since she is prohibited to get married again because she is still bound in a wedlockthe marriage is illegitimate. The settlement of the dispute between husbandand wife at Meunasah Papeun village is be negotiation, a meeting leading to consensus by presenting a fair and wise judge from both sides in order to settle the couple Keywords: Settling Syiqaq (Dispute), Marriage Law, the Islamic Law